HARMONIZING THREE-PHASE AC GRIDS A DUAL APPROACH COMPARISON OF PV-BATTERY ENERGY STORAGE SAPF CONTROLS - Tripathy, Omkar; Parida, Sritam; Prasad Behera, Maheswar; Sahu, Manoj Kumar; Anitha, E. Baby; Perumal, Maniraj; Arif, Mohammad; Kumar C, Venkatesh (Journal of mechanics of continua and mathematical sciences, 2025)
This paper investigates the effectiveness of two control approaches, Photovoltaic (PV)-Battery Energy Storage Systems (BESS) and SAPF, in harmonizing three-phase AC grids, focusing on power quality (PQ) and dq transformation theory. With the rising integration of renewable energy sources (RES), such as PV systems, ensuring PQ becomes critical. The dual approach comparison aims to assess the performance and suitability of these control strategies. The PV-BESS system utilizes batteries to store excess PV-generated energy, offering grid flexibility and improving stability. Conversely, SAPF controls utilize power electronics to address harmonics and reactive power fluctuations, thereby enhancing grid reliability. Through simulation and analysis, this study evaluates the efficacy, cost-effectiveness, and practicality of both approaches in PQ improvement using dq theory. The findings contribute to advancing grid integration techniques, optimizing renewable energy utilization, and ensuring a robust and stable power supply infrastructure, guided by PQ and dq transformation theory principles.